2016
DOI: 10.4253/wjge.v8.i20.770
|View full text |Cite
|
Sign up to set email alerts
|

Identification of factors associated with sedation tolerance in 5000 patients undergoing outpatient colonoscopy: Canadian tertiary center experience

Abstract: AIMTo develop a prediction model aimed at identifying patients that may require higher than usual sedation doses during colonoscopy.METHODSA retrospective chart review on 5000 patients who underwent an outpatient colonoscopy at St. Paul’s Hospital from 2009 to 2010 was conducted in order to develop a model for identifying patients who will require increased doses of sedatives. Potential predictor variables including age, gender, endoscopy indication, high sedation requirements during previous endoscopies, diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 6 publications
0
6
1
1
Order By: Relevance
“…Contrary to other studies, our findings suggest that females have lower sedation requirements as compared to males[ 7 , 11 , 23 ]. Alternatively, one prospective cohort study found that gender has no impact on sedation requirements during endoscopy[ 12 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to other studies, our findings suggest that females have lower sedation requirements as compared to males[ 7 , 11 , 23 ]. Alternatively, one prospective cohort study found that gender has no impact on sedation requirements during endoscopy[ 12 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Finally, another factor associated with worse tolerance in our study was the endoscopist's subjective assessment of a difficult exploration. This perception was also considered as being associated with worse tolerance in a retrospective study, in an indirect way, taking into account the need for increased sedation rather than the VAS assessment (18). There is no established definition of a difficult colonoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Others have associated poor tolerance with aspects related to both the exploration and the diagnostic procedure itself, including the reason for the procedure as well as the duration and difficulty of the colonoscopy. However, the methodology used in these studies varies considerably since many of them analyze oral endoscopy and colonoscopy together, whilst others include unsedated patients or assess tolerance through indirect methods such as the use of higher doses of sedatives (11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Furthermore, no studies with these characteristics have been found in our context.…”
Section: Introductionmentioning
confidence: 99%
“…131 A retrospective analysis of 5282 patients who underwent an outpatient colonoscopy associated the previous diagnosis of IBD with higher demand of sedation. 132,133 Therefore, endoscopic procedures in IBD patients should be performed under deep sedation instead of conscious sedation or no sedation. Propofol-based sedation is currently the best option for deep sedation in most cases, and should be administered by an endoscopist, anaesthesiologist, or trained nurse according to country-specific regulation.…”
Section: Sedationmentioning
confidence: 99%